2021
DOI: 10.1097/ta.0000000000003083
|View full text |Cite
|
Sign up to set email alerts
|

A clinical practice guideline using percentage of predicted forced vital capacity improves resource allocation for rib fracture patients

Abstract: BACKGROUND:Predicting rib fracture patients that will require higher-level care is a challenge during patient triage. Percentage of predicted forced vital capacity (FVC%) incorporates patient-specific factors to customize the measurements to each patient. A single institution transitioned from a clinical practice guideline (CPG) using absolute forced vital capacity (FVC) to one using FVC% to improve triage of rib fracture patients. This study compares the outcomes of patients before and after the CPG change. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Pain management improves vital capacity, chest expansion and inspiratory capacity. This implies a shorter hospital stay and more efficiency in performing breathing exercises and mobilization [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…Pain management improves vital capacity, chest expansion and inspiratory capacity. This implies a shorter hospital stay and more efficiency in performing breathing exercises and mobilization [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…Brandon et al [38] reported that RibScore, a radiographic score based on fracture pattern which includes six variables (namely ≥ 6 rib fractures, bilateral fractures, flail chest, ≥ 3 severely displaced fractures, first rib fracture, and at least one fracture in anterior, lateral, and posterior areas), was associated with complications and adverse pulmonary outcomes. More recently, Billings et al [39] and Khan et al [40] showed that rib fracture patients triaged based on forced vital capacity had shorter ICU-LOS and HLOS with 78% lower odds of ICU transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Our institution uses a prospectively validated clinical practice guideline (CPG) utilizing percent of predicted forced vital capacity (FVC%) to determine level of care for trauma patients with rib fractures. [10][11][12] We sought to compare frailty metrics with FVC% in predicting adverse outcomes. We hypothesized that frailty metrics will be more predictive of adverse outcomes than FVC% and improve triage of geriatric patients with rib fractures.…”
Section: Introductionmentioning
confidence: 99%